2020
DOI: 10.1186/s12948-020-00130-9
|View full text |Cite
|
Sign up to set email alerts
|

Allergic rhinitis and asthma symptoms in a real-life study of MP-AzeFlu to treat multimorbid allergic rhinitis and asthma

Abstract: Background: Asthma affects up to nearly 40% of patients with allergic rhinitis (AR). Poor control of AR symptoms is associated with poor asthma control. The goal of this study was to evaluate the effect of AR treatment with MP-AzeFlu on symptoms of AR as well as symptoms of asthma. Methods: This prospective study used a visual analog scale (VAS) to assess symptoms of AR and asthma before and after treatment with MP-AzeFlu (Dymista ® ; azelastine hydrochloride plus fluticasone propionate; 1 spray in each nostri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…Among patients with AR and comorbid asthma, MP-AzeFlu improved VAS scores across all study parameters, including AR symptoms, sleep quality, daily work or school activities, daily social activities, and daily outdoor activities. Asthma symptom severity improved by 24.8 mm on the VAS along with reduction in usage of asthma reliever medication [61].…”
Section: Real-life Datamentioning
confidence: 93%
See 1 more Smart Citation
“…Among patients with AR and comorbid asthma, MP-AzeFlu improved VAS scores across all study parameters, including AR symptoms, sleep quality, daily work or school activities, daily social activities, and daily outdoor activities. Asthma symptom severity improved by 24.8 mm on the VAS along with reduction in usage of asthma reliever medication [61].…”
Section: Real-life Datamentioning
confidence: 93%
“…In general, MP-AzeFlu was well-tolerated in clinical [52,62] and real-life studies [9,61], with no safety findings that would preclude its long-term use. Most of the adverse events (AEs) were mild-to-moderate in severity and unrelated to treatment.…”
Section: Safety and Tolerabilitymentioning
confidence: 97%
“…Dalam penelitian tersebut sebanyak 146 dari 267 orang (54,7%) yang memiliki rinitis alergi disertai asma berjenis kelamin perempuan. 24 Prevalensi rinitis alergi dan asma lebih banyak ditemukan pada laki-laki saat usia anak hingga mendekati masa pubertas. Namun, saat masa pubertas sekitar usia 10-18 tahun, prevalensi rinitis alergi dan asma ditemukan paling banyak pada perempuan.…”
Section: Pembahasanunclassified
“…However, the literature is scarce and inconclusive regarding how seasonality and severity of AR may influence its association with mental illness 9,10 . In fact, although it has been shown that an effective control of AR is important for the prevention or reduction of some of its comorbidities (such as sleep disorders, allergic conjunctivitis, or asthma exacerbations), 11 the association between AR control in the frequency of anxiety and depression symptoms has not yet been fully described 12–14 …”
Section: Introductionmentioning
confidence: 99%